(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Intracranial foreign bodies (ICFBs) are uncommon and often lead to significant complications during hospital care. [...] This case highlights careful forensic evaluation before classifying injuries as grievous or simple.